2019
DOI: 10.1097/md.0000000000017099
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tai Chi alone or as additional therapy on low back pain

Abstract: Background:This is the first systematic review evaluating and statistically synthesis the current studies regarding the effects of Tai Chi on pain and disability in patients with low back pain (LBP).Methods:Seven electronic databases including PubMed, EMBASE, Web of Science, Cochrane Library, China National Knowledge Infrastructure (CNKI), Wanfang and VIP information from inception to early March 2019 were searched. The Physiotherapy Evidence Database (PEDro) Scale was used to assess quality of all included ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…When combining this outcome measured on different scales, the standardized mean difference (SMD) with 95% confidence intervals (CI) were used. Meanwhile, subgroup analysis based on scales with the mean difference and 95% confidence intervals were conducted [18]. Statistical heterogeneity among the studies was assessed by the chi-square test and I 2 value.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…When combining this outcome measured on different scales, the standardized mean difference (SMD) with 95% confidence intervals (CI) were used. Meanwhile, subgroup analysis based on scales with the mean difference and 95% confidence intervals were conducted [18]. Statistical heterogeneity among the studies was assessed by the chi-square test and I 2 value.…”
Section: Plos Onementioning
confidence: 99%
“…18 RCTs were included for qualitative and quantitative analysis. The detailed information of the flowchart about searching and including studies was shown inFig 1.…”
mentioning
confidence: 99%
“…There is nothing to prevent the association of this practice with other therapeutic resources. As suggested by Qin et al (2019) [23] in recent meta-analysis, both the practice of TCC alone or as an additional therapy associated with physical therapy can decrease pain and improve disability in patients with low back pain. Meta-analysis studies [6,17,24,25,26,27] reinforce scientific evidence of TCC.…”
Section: Resultsmentioning
confidence: 99%
“…Tai chi is a traditional Chinese martial art that uses a series of slow, controlled movements to improve balance, strength, flexibility, relaxation, and mental concentration. 7 A randomized controlled trial 74 in Medicine concluded that tai chi alone or along with physical therapy may be beneficial for individuals with lower back pain. Another randomized study by Liu et al 75 found that tai chi reduced lower back pain in adults aged 50 years and older.…”
Section: Lifestyle Interventionsmentioning
confidence: 99%